RNase III coding genes modulate the cross-kingdom biofilm of Streptococcus mutans and Candida albicans - Lu, Yangyu; Lei, Lei; Deng, Yalan; Zhang, Hongyu; Xia, Mengying; Wei, Xi; Yang, Yingming; Hu, Tao (Frontiers in Microbiology, 2022)
Streptococcus mutans constantly coexists with Candida albicans in plaque-biofilm of early childhood caries (ECC) of which the pathogenesis can be influenced by the interactions between S. mutans and C. albicans through the exopolysaccharides. Our previous studies have shown that rnc, the gene coding Ribonuclease III (RNase III) of S. mutans, is implicated in the cariogenicity of S. mutans by regulating the exopolysaccharides metabolism. The DCR1 gene in C. albicans codes the sole functional RNase III and is capable of the production of non-coding RNAs. However, whether rnc or DCR1 can regulate the structure and the cariogenic virulence of the cross-kingdom biofilm of S. mutans and C. albicans has been not well understood yet. The current study aimed to investigate the roles of DCR1 and rnc in modulating the biological characteristics of the dual-species biofilm of S. mutans and C. albicans and to reveal the molecular mechanism of regulation. DCR1 low-expressing and over-expressing strains were constructed. The morphology, biomass and the exopolysaccharides or lactic acid production of the dual-species biofilm were assessed. RT-qPCR and transcriptomic profiling were performed to unravel molecular pathways and mechanism of regulation of rnc on the virulence of C. albicans. We found that both rnc and DCR1 could regulate the biological characteristics of cross-kingdom biofilm. The rnc gene prominently contributed to the formation of dual-species biofilm by positively modulating the extracellular polysaccharides synthesis of biofilm and the virulence as well as polysaccharide or pyruvate metabolism pathways of C. albicans, leading to increased biomass, biofilm roughness and acid production, which facilitated the assembly of a cariogenic cross-kingdom biofilm and the generation of an augmented acidic milieu. These results may provide an avenue for exploring new targets for the effective prevention and treatment of ECC.